SARS-CoV-2, Lung Protective Ventilation, Low Middle Income Countries, and Pediatric Intensivists as Cross Disciplinary Knowledge Translation and Implementation Science Specialists. (March 2022) - Seepersaud, M.; Marrero, A.; Davidson, T.; Smith, S.
Abstract : Purpose: We hypothesized that despite the low incidence of severe SARS-CoV-2 infections in children in Guyana, due to their specific skillset in lung protective ventilation, our Pediatric Intensivists were uniquely positioned to address significant training and readiness gaps in our colleagues attending a surging critically ill Adult COVID-19 patient population. Methods & Materials: In Guyana, there are few clinicians trained in Critical-Care Medicine (CCM). The high incidence of ventilator dependence in seriously ill SARS-CoV2 patients, combined with a dearth of CCM practitioners competent in complex mechanical ventilation management left Guyana ill prepared to manage these patients. This knowledge deficit was further exacerbated in that many clinicians at our National Infectious Diseases Hospital were co-opted into CCM roles from other specialties with little to no CCM training. We have a very small core of Pediatric Surgical Critical Care Medicine staff that was formally trained in PCCM outside of Guyana. This core was instrumental in establishing a unique and formal Pediatric Critical-Care Medicine Micro-Modular Fellowship (PCCM-MMF) program that allowed the creation of Guyana's only Pediatric ICU. A significant number of that core are also involved in Guyana's National COVID Task Force. Given that all graduates of our PCCM-MMF program are extensively trained in Lung Protective Ventilation, it was very appropriate to utilize them to augment Adult critical care capacity. Thirty physicians with primarily adult practices and little to no previous knowledge of ventilator management were enrolled in a multi-modal triphasic mechanical ventilation short course facilitated by PCCM staff. Results: We were able to rapidly enable two cohorts of 15 Adult clinicians to competently address critical knowledge deficits and staffing shortfalls. We improved morbidity and mortality amongst our mechanically ventilated adult COVID-19 patients, as well as relieved significant multifactorial caregiver strain. Conclusion: Our successful utilization of PCCM staff as Mechanical Ventilation didactic and clinical educators for an Adult patient population carries implications for cross disciplinary Knowledge Translation and Implementation Science in a wide variety of practice milieus. We are actively pursuing research opportunities to further experiment with other skill sets incorporated in our PCCM Micro-Modular Fellowship and welcome potential collaborators.